The EU-FP7 Project SUCCESS – Scale-up of Oxygen Carrier for Chemical Looping Combustion using Environmentally Sustainable Materials. (July 2017) - Penthor, Stefan; Mattisson, Tobias; Adánez, Juan; Bertolin, Stéphane; Masi, Enrica; Larring, Yngve; Langørgen, Øyvind; Ströhle, Jochen; Snijkers, Frans; Geerts, Lieve; Albertsen, Knuth; Williams, Gareth; et al.
Abstract: The paper gives a high level overview of the work performed in the EU-FP7 funded project SUCCESS (Scale-up of oxygen carrier for chemical looping combustion using environmentally sustainable materials). The project is the most recent one in a series of successful EU-funded research projects on the chemical looping combustion (CLC) technology. Its main objective is to perform the necessary research in order to demonstrate the CLC technology in the range of 10 MW fuel power input. The main focus is on scale-up of production of two different oxygen carrier materials using large scale equipment and industrially available raw materials. This will guarantee availability of oxygen carrier material at tonne scale. The scale-up of the two materials, a Cu and a Mn based, was successful and first tests with the Cu material have already been performed in four different pilot units up to 150 kW where the material showed excellent performance regarding fuel conversion. In addition to technology scale-up, extensive end-user evaluation is performed. This evaluation includes investigations on health, security and environmental impacts (HSE), a life cycle analysis and a techno-economic analysis to compare the CLC technology for steam generation against the current state-of-the-art technologies.